Improvement of the Technology of Obtaining Pectin from Local Raw Materials (Eurasian Scientific Herald, 2023)
Modernization of processing and production in our country, technical re-equipment and production of finished products from raw materials, as well as the production of pectin, as well as filling the domestic market through the widespread introduction of waste-free equipment and innovative technologies, are considered important to be urgent issues of today.